Quality of life in episodic hypoxic children after emergency department or PICU hospitalization - Yuniar, Irene; Julianti, Julianti; Gunardi, Hartono; Dewi, Rismala; Wiguna, Tjhin; Lubis, Munar (Indonesian Pediatric Society, 2025)
Background Studies on long–term outcomes of hypoxic children after being hospitalized are limited, even though hypoxia is known to affect their quality of life (QoL). Objective To assess the QoL of children with episodic hypoxia following hospitalization in the emergency department (ED) and Pediatric Intensive Care Unit (PICU). Methods A prospective cohort design study targeting pediatric patients aged 2–7 years with critical illness was conducted at Dr. Cipto Mangunkusumo Hospital. Inclusion criteria are hypoxia patients receiving oxygen therapy, defined from the ratio of partial arterial oxygen pressure and inspired oxygen (PaO2/FiO2). The PedsQLTM questionnaire was used to assess QoL at the time of admission and 3 months after hypoxia event. Patients with cerebral palsy, mental retardation, chromosomal abnormalities, liver transplantation, and length of stay ≤24 hours were excluded. Data distribution in numerical form was analyzed using the Kolmogorov–Smirnov test. Results Forty-six children with a median age of 4 (2–7) years had decreased QoL at 3 months after episodic hypoxia, based on PedsQLTM scores. The physical, emotional, and social domains were significantly decreased (P<0.01) compared to QoL at the time of admission. Prior to admission, 78.3% of children had already experienced impaired QoL. Conclusion Children with episodic hypoxia demonstrated a decline in QoL at 3 months after hypoxia event based on PedsQLTM scores. Specifically, the physical, emotional, and social domains were significantly decreased compared to at the time of admission.